2007
DOI: 10.1103/physrevb.76.085332
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative versus molecular adsorption of phenol onSi(100)2×1: A first-principles calculation

Abstract: We investigated the competitive adsorption of a bifunctional molecule, phenol, on Si͑100͒2 ϫ 1 by ab initio calculations. We performed geometry optimizations of phenol adsorbed either molecularly or dissociatively, on five possible sites ͑top, bridge, valley bridge, cave, and pedestal͒, in the low coverage regime. We found that the dissociative adsorption of phenol on top of a silicon dimer is the most favorable adsorption configuration. In the group of dissociative adsorption the phenol initially placed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…1c-n along with the reference single adsorbate models as obtained in Ref. [9] (Fig. 1a is the single molecule on-top adsorption, 1b the bridge molecular one).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1c-n along with the reference single adsorbate models as obtained in Ref. [9] (Fig. 1a is the single molecule on-top adsorption, 1b the bridge molecular one).…”
Section: Resultsmentioning
confidence: 99%
“…the bridge and the on-top ones, respectively [9], were used as starting models for the multi-molecules adsorption. The geometrical outcome of the optimization is reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend has been found previously for benzene 31 and for chloro-and dichlorobenzene. 32 For a 0.5 ML coverage, the energetically most favorable structure is F, which is by 0.8-0.9 eV lower in energy than the next lowest energy structure C. However, according to the revPBE calculations D is 0.15 eV more favorable than E, whereas according to PW91 and PBE calculations E is 0.22-0.23 eV more favorable than D. Carbone et al 5 used firstprinciples calculations with the BLYP functional 14,15 to study structures A and D on various adsorption sites and found the adsorption energies of 0.55 eV and 2.56 eV, respectively. This is in good agreement with our B3LYP results and the small differences are presumably due to the differences between BLYP and B3LYP functionals and the different coverages of 1 6 ML and 0.5 ML used in their and the present calculations, respectively.…”
Section: Neglecting Van Der Waals Interactionsmentioning
confidence: 98%
“…The theoretical study by Carbone et al 5 focused on possible adsorption sites for the non-dissociated butterfly structure ͑structure A in Fig. 1͒ and the above-mentioned dissociative structure.…”
Section: Introductionmentioning
confidence: 99%